Ambulatory reflux monitoring for diagnosis of gastro‐esophageal reflux disease: Update of the Porto consensus and recommendations from an international consensus group. Issue 10 (31st March 2017) - Roman, S.; Gyawali, C. P.; Savarino, E.; Yadlapati, R.; Zerbib, F.; Wu, J.; Vela, M.; Tutuian, R.; Tatum, R.; Sifrim, D.; Keller, J.; Fox, M.; et al.
Abstract: Background: An international group of experts evaluated and revised recommendations for ambulatory reflux monitoring for the diagnosis of gastro‐esophageal reflux disease (GERD). Methods: Literature search was focused on indications and technical recommendations for GERD testing and phenotypes definitions. Statements were proposed and discussed during several structured meetings. Key Results: Reflux testing should be performed after cessation of acid suppressive medication in patients with a low likelihood of GERD. In this setting, testing can be either catheter‐based or wireless pH‐monitoring or pH‐impedance monitoring. In patients with a high probability of GERD (esophagitis grade C and D, histology proven Barrett's mucosa >1 cm, peptic stricture, previous positive pH monitoring) and persistent symptoms, pH‐impedance monitoring should be performed on treatment. Recommendations are provided for data acquisition and analysis. Esophageal acid exposure is considered as pathological if acid exposure time (AET) is greater than 6% on pH testing. Number of reflux episodes and baseline impedance are exploratory metrics that may complement AET. Positive symptom reflux association is defined as symptom index (SI) >50% or symptom association probability (SAP) >95%. A positive symptom‐reflux association in the absence of pathological AET defines hypersensitivity to reflux. Conclusions and Inferences: The consensus group determined that grade C or D esophagitis, peptic stricture, histology proven Barrett's mucosa >1 cm, and esophageal acid exposure greater >6% are sufficient to define pathological GERD. Further testing should be considered when none of these criteria are fulfilled. Abstract : The consensus group proposes to define pathological GERD as at least one of the following criteria: Grade C or D esophagitis, peptic stricture, Barrett's mucosa >1 cm and esophageal acid exposure >6%. Number of reflux episodes and baseline impedance should be considered as exploratory tools for further research.